THE USE OF FIGURE OF SPEECH IN GURINDAM 12 BY RAJA ALI HAJI: AN ANALYSIS OF ITS KIND AND FUNCTION - Zia Hisni Mubarak; Gaguk Rudianto (eScience Humanity Journal, 2022)
Gurindam is an old type of poetry consisting of two lines of content which usually contains satire and advice. One of the famous Gurindam in Malay culture of Riau Kepulauan is Gurindam 12 by Raja Ali Haji. The purpose of this study is to analyze the types of affirmative figure of speech used in Gurindam 12. This study used qualitative methods in reviewing the available data and provides a description of the resulting study. The form of this research is a literature review in the form of local wisdom where the research team examines Gurindam 12. The data is then analyzed by looking at the types (its kind) of figure of speech and the meanings (its function) contained in the Gurindam (Kosasih, 2011). From the study it is found that there are 18 data analyzed as affirmative figure of speech where 3 data is included as pleonasm, 6 data of repetition and 9 data of parallelism. The use of affirmative figure of speech in Gurindam 12 is because the contents of this poem are doctrinal teachings related to religion. The reason is that when Gurindam 12 was created, the majority of the Malay population in the Riau Archipelago was Muslim.